Novel real-time system design for floating-point sub-Nyquist multi-coset signal blind reconstruction - Yin, Hong Xu (Nanyang Technological University, 2015)
We propose a novel real-time system design for multiband signal blind reconstruction using multi-coset sampling theory. Multi-channel signals are acquired under sub-Nyquist sampling frequency to perfectly reconstruct the original signal spectrum. A novel system design with Field-Programmable Gate Array (FPGA) implementation is presented in this report. There are two main contributions introduced by this design. Firstly, the FPGA system uses 32-bit single precision floating point dataflow rather than conventional 16-bit fixed point to recover signals with much lower Signal-Noise Ratio (SNR). Secondly, we introduce a novel Jacobi CORDIC eigenvalue decomposition (EVD) core using parallel pivot-seeking circuit and parallel 3-CORDIC design to improve speed significantly. Hermitian matrices of dimensions from 2 to 10 are tested to compare conventional 2-CORDIC EVD and the proposed EVD. The proposed EVD effectively reduces on average 36% of processing time for mesh connection system and over 50% for parallel system. Part of this final year project was written as a conference paper accepted by the 2015 Annual International Symposium of Circuits and Systems (ISCAS 2015) for lecture presentation on May 25, 2015. The conference is to be held at the Cultural Centre of Belem, Lisbon, Portugal from May 24 – 28, 2015.